1989
DOI: 10.1017/s0043174500071897
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Methods for Measuring Effects of Density and Proportion in Plant Competition Experiments

Abstract: Three approaches to data analysis were compared to describe competitive interactions between wheat and Italian ryegrass. Replacement series were performed using the two species at total densities of 100, 200, and 400 plants/ m2, and separate monoculture experiments for each species at densities from 33 to 800 plants/m2. Approaches to data analysis included: 1) conventional analysis of replacement series experiments, 2) development of synthetic no-interaction responses from monoculture experiments for compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
13

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 12 publications
1
53
0
13
Order By: Relevance
“…High intraspecific and interspecific competition of potato clearly suggests that potato plants have captured environmental resources more efficiently than common bean plants. Roush et al (1989) also reported that NDI was smaller than 1 for wheat and ryegrass intercropping. In contrast, Raey et al (2005) in soybean and shatter cane interference and Passini et al (2003) in Alexander grass and common bean competition reported that NDI was greater than 1.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…High intraspecific and interspecific competition of potato clearly suggests that potato plants have captured environmental resources more efficiently than common bean plants. Roush et al (1989) also reported that NDI was smaller than 1 for wheat and ryegrass intercropping. In contrast, Raey et al (2005) in soybean and shatter cane interference and Passini et al (2003) in Alexander grass and common bean competition reported that NDI was greater than 1.…”
Section: Discussionmentioning
confidence: 94%
“…Roush et al (1989) compared three approaches to describe competitive interactions between wheat and Italian ryegrass. These comprised conventional analysis of replacement series experiments, development of synthetic no-interaction responses from monoculture experiments for comparison with results from mixedculture, and responses of the reciprocal yield of individual plants to variation in densities of the two species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This wider spacing resulted in the same density of each species as the 0.5:0.5 species proportions for the mixed stands when planted on the 3 m × 3 m grid. Thus, the monoculture treatments at the widest spacing (4.2 m × 4.2 m) can be compared with 0.5:0.5 species proportions at 3 m × 3 m spacing and also allow an assessment of the effect of other densities on the outcome of the species association (Jolliffe et al 1984;Firbank and Watkinson 1985;Roush et al 1989). …”
Section: Experimental Designmentioning
confidence: 99%
“…Experiment designs that allow the full implementation of the RGRD method include those that have been proposed for response surface estimation (e.g. Connolly 1987;Rejma´nek et al 1989;Roush et al 1989;Snaydon 1991;Turkington and Jolliffe 1996;Gibson et al 1999;Goldberg and Scheiner 2001;Inouye 2001).…”
Section: Discussionmentioning
confidence: 99%